SPATIAL-TEMPORAL PATTERNS OF COFFEE TREE PHYSIOLOGY - Santini, Paula Tristão; Barbosa, Ronei Aparecido; Almeida, Lorena Gabriela; de Souza, Kamila Rezende Dazio; Barbosa, João Paulo Rodrigues Alves Delfino; Alves, José Donizeti (Coffee Science - ISSN 1984-3909, 2019)
The ecophysiological parameters of coffee canopy were mapped throughout the day. Therefore, evaluations were carried out in ‘Catuaí Vermelho’ Coffea arabica L., measuring 1.7 meters. A vertical gradient (from the apex to the base of the plant canopy) and a horizontal gradient (plagiotropic branches) were established to analyze different positions of the canopy. Thus, in the vertical direction, four heights were analyzed in the plant: top, upper, middle and lower regions. In the horizontal gradient, the plagiotropic branches were divided into three parts: basal, median and apical. Collection was performed on the east and west sides of the canopy, at four times of the day: 6 a.m., 9 a.m., noon, and 3 p.m., totaling 24 collection points at each time. Gas exchange, photosynthetically active radiation and leaf temperature were evaluated in each of the 24 points of the coffee canopy. The gas exchange characteristics of an individual coffee leaf diverge considerably from other leaves, which require caution when scaling estimates of leaf photosynthesis at the global canopy level. The analysis of some punctual leaves does not serve to discriminate the overall dynamics of a canopy.